Evaluation of Patient Satisfaction as a Quality Indicator in the Ophthalmology Service of Hospital Central de San Cristóbal Under the SERVQUAL Quality Model - Carmen Soraida Niño de Pernia; Alexis Isauro Apolinar Márquez; Nicolás Castillo Pinillos; Doris Romelia Rozo Fernández; Angela Verónica Villamizar Gutiérrez; Daicy Yasmin Gómez Bueno (International Journal of Scientific Research and Modern Technology, 2026)
This study aims to analyze the Ophthalmology Service of the Hospital Central de San Cristóbal to design and propose a systematic tool, based on the SERVQUAL model, aimed at assessing patient satisfaction, thereby transforming user perception into a key indicator for evidence-based clinical management. Theoretical Framework: From a theoretical standpoint, the research conceives healthcare quality as a management imperative sustained by user experience, approaching this evaluation from a transcomplexity perspective by understanding that satisfaction is a phenomenon involving medical, administrative, ethical, and human dimensions. Methodology: Methodologically, technological-propositive research was developed with a non-experimental, cross-sectional design, employing an 11-item structured instrument with a five-point Likert scale; this tool evaluates the five dimensions of healthcare quality (tangibles, reliability, responsiveness, assurance, and empathy), and its content validity was duly certified through expert judgment. Results: Regarding general results, it was evidenced that the dimensions with the greatest strengths were Assurance (mean of 4.61) and Empathy (4.50 and 4.52), which driven a high Global Satisfaction (4.62). In contrast, the areas of opportunity with the lowest scores were Reliability (3.55) and Responsiveness (3.83), heavily affected by unpunctuality and prolonged waiting times. Conclusions: Based on these findings, it is concluded that, while the service boasts solid technical and human strengths that generate trust and loyalty, operational inefficiency in time control represents the critical link restricting excellence. Consequently, it is recommended to implement an optimization plan focused on appointment automation and the standardization of care times to consolidate a comprehensive quality service.